Comparison of five agglutination tests for identification of Staphylococcus aureus. - Wilkerson, M (1997)
Various commercially produced agglutination kits are widely used for the identification of Staphylococcus aureus. These kits detect the presence of protein A and/or clumping factor on S. aureus. The literature has shown that methicillin-resistant S. aureus (MRSA) isolates which are deficient in both clumping factor and protein A may be misidentified. Two products, Slidex and Staphaurex Plus, utilize specific anti-S. aureus antibodies, potentially giving them greater sensitivity compared to products without these antibodies. We report a prospective study designed to compare the performance characteristics of Fastaph, Slidex, Staphaurex, Staphaurex Plus, Staphyloslide, and the tube coagulase test for the identification of staphylococcal isolates. All discrepant isolates were tested with the Gen-Probe AccuProbe S. aureus test and were identified to the species level with conventional reference biochemicals. A total of 1,193 isolates were tested, including 33 MRSA and 423 methicillin-sensitive S. aureus isolates. The sensitivities and specificities of the tests, respectively, were as follows: Fastaph, 99.1 and 98.9%; Slidex, 99.6 and 96.4%; Staphaurex, 98.9 and 99.9%; Staphaurex Plus, 99.6 and 93.9%; Staphyloslide, 99.1 and 98.9%; and tube coagulase, 99.3 and 100%. Sensitivity was excellent for all of the products tested. The specificities of Fastaph, Staphaurex, and Staphyloslide were excellent, while Staphaurex Plus and Slidex demonstrated less optimal results.